2004
DOI: 10.3201/eid1004.030271
|View full text |Cite
|
Sign up to set email alerts
|

Dengue 3 Epidemic, Havana, 2001

Abstract: In June 2001, dengue transmission was detected in Havana, Cuba; 12,889 cases were reported. Dengue 3, the etiologic agent of the epidemic, caused the dengue hemorrhagic fever only in adults, with 78 cases and 3 deaths. After intensive vector control efforts, no new cases have been detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 9 publications
1
59
0
7
Order By: Relevance
“…IgM dengue antibodies were positive in more than 12,000 patients, including 81 DHF cases. 6 Data obtained from laboratory surveillance during the epidemic confirmed that the DEN 3 virus was the only etiological agent of this outbreak. Ninetyone DEN 3 isolates were obtained at different times of the epidemic.…”
Section: Introductionmentioning
confidence: 76%
“…IgM dengue antibodies were positive in more than 12,000 patients, including 81 DHF cases. 6 Data obtained from laboratory surveillance during the epidemic confirmed that the DEN 3 virus was the only etiological agent of this outbreak. Ninetyone DEN 3 isolates were obtained at different times of the epidemic.…”
Section: Introductionmentioning
confidence: 76%
“…The effective vector control activities avoided the spread of the virus to other parts of the country allowing the elimination of transmission in the same year [17]. Later, a DENV-3 outbreak took place in Havana in 2001/2002 with 81 DHF cases and total of 12,889 cases [19]. Vector control measures limited once again the extension of this virus to the rest 14 Cuban provinces.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to other countries, characterized by the cocirculation of several serotypes, Cuba represents a unique scenario to perform genetic studies of DHF resistance and susceptibility, with known clinical and serologic dengue markers in a population with a unique history of dengue virus epidemics [11,14,15,28]. Consequently, in this study, HLA-A, -B, class I, and HLA-DRB1 class II polymorphism were examined in Cuban individuals with history of DF or DHF in the course of both primary and secondary dengue 2 infections during the 1997 D2 outbreak, using PCR-based typing techniques.…”
Section: Introductionmentioning
confidence: 99%